2022
DOI: 10.3390/ijerph191610273
|View full text |Cite
|
Sign up to set email alerts
|

A Benefit-Cost Analysis of BackTrack, a Multi-Component, Community-Based Intervention for High-Risk Young People in a Rural Australian Setting

Abstract: BackTrack is a multi-component, community-based program designed to build capacity amongst high-risk young people. The aim of this study was to conduct a benefit-cost analysis of BackTrack, which was implemented in Armidale, a rural town in New South Wales, Australia. Costs and benefits were identified, measured and valued in 2016 Australian dollars. Costs were estimated from program financial and administrative records. Benefits were estimated using a pre-post design and conservative economic assumptions. Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A cost -benefit analysis on the ADTRAC programme showed a cost benefit ratio of £1.11 benefit for each £1 invested (Burgess et al, 2021). A similar study called BackTrack conducted in a rural Australian setting found evidence of significant quantifiable improvements in several outcomes: high school attendance or completion, vocational education attendance or completion, unskilled or vocationally qualified employment and economic productivity as well as reduced homelessness, engagement with health services, acquisition of job readiness skills, as well as reduced local infrastructure vandalism and reduced crime (Deeming et al, 2022). In the BackTrack study, ‘high risk’ was defined as the increased likelihood of criminal activity, lack of employment, mental health issues, alcohol and substance abuse and lack of engagement with the health care system.…”
Section: Young People and Paid Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A cost -benefit analysis on the ADTRAC programme showed a cost benefit ratio of £1.11 benefit for each £1 invested (Burgess et al, 2021). A similar study called BackTrack conducted in a rural Australian setting found evidence of significant quantifiable improvements in several outcomes: high school attendance or completion, vocational education attendance or completion, unskilled or vocationally qualified employment and economic productivity as well as reduced homelessness, engagement with health services, acquisition of job readiness skills, as well as reduced local infrastructure vandalism and reduced crime (Deeming et al, 2022). In the BackTrack study, ‘high risk’ was defined as the increased likelihood of criminal activity, lack of employment, mental health issues, alcohol and substance abuse and lack of engagement with the health care system.…”
Section: Young People and Paid Employmentmentioning
confidence: 99%
“…Employment-related benefits of the intervention included educational attendance or completion of education, increased employment, and economic productivity. The analysis of the BackTrack intervention produced a net social benefit of $3,267,967, with a return on investment (ROI) of $2.03 for every $1 invested (Deeming et al, 2022). Both ADTRAC and BackTrack aim to address the needs of high-risk young people.…”
Section: Young People and Paid Employmentmentioning
confidence: 99%